Implementing Blockchain in Higher Education: Technical Architecture, Administrative Challenges, and Policy Directions for Nepal and Least Developed Countries (OCEM Journal of Management, Technology & Social Sciences, 2026)
This systematic literature review investigates the implementation of blockchain technology in higher education for academic credential issuance, record verification, and trust-building across institutions, with a focus on Nepal and similar least-developed-country contexts. This review is organised based on three research questions, which are proposed technical architecture, administrative and infrastructural barriers to adoption, and policy requirements for secure and credible implementation. Reliable, published, and influential sources were identified through a PRISMA-inspired search and screening protocol, including peer-reviewed journal articles, indexed conference proceedings, and official legal and standards documents. A total of two hundred and fourteen (N = 214) papers were screened, and seventeen (n = 17) core sources were included for qualitative synthesis.The results show that blockchain-based credentialing is technically mature at the prototype level. They further show that many proposed systems have layered architecture consisting of an application interface, an identity and credential layer, a blockchain ledger, and off-chain storage. Empirical findings show that blockchain success depends not only on application but also on legal recognition, institutional readiness, interoperability, privacy protection, key management, and employer-side verification. However, in Nepal’s case, the review argues that the direct implementation within the country may be early. A strong policy approach is needed, beginning with legal recognition of digital and blockchain-verifiable credentials, adoption of W3C Verifiable Credentials and Decentralised Identifiers, small university pilots, privacy impact assessment, onboarding of public-sector verifiers, and planning for failed or abandoned systems. The review concludes that blockchain can support academic credential verification in Nepal and similar contexts, but it needs to be viewed as a long-term institutional infrastructure.